Measuring the States of Language Against the Conditions of the World: A Study in Grammatical Thought - malawi, amine (El Omda in Linguistics and Discourse Analysis, 2018)
The approach of grammarians goes beyond merely analyzing linguistic phenomena to questioning the underlying intellectual foundations behind the utterance. It follows a reasoning-based method, centered on constructing a conception of the Arabic language in relation to the laws of the universe and the states of the world. The aim is to demonstrate that the linguistic system derives its characteristics from an external reality, articulated within a linguistic context and unified by the principles of wisdom. Thus, existence manifests in verbal states, which constitute part of this system, establishing both the legitimacy of reasoning and the methodology of scholarly inquiry.